History and contemporary significance of the Rhynie cherts—our earliest preserved terrestrial ecosystem. (18th December 2017) - Edwards, Dianne; Kenrick, Paul; Dolan, Liam
Abstract : The Rhynie cherts Unit is a 407 million-year old geological site in Scotland that preserves the most ancient known land plant ecosystem, including associated animals, fungi, algae and bacteria. The quality of preservation is astonishing, and the initial description of several plants 100 years ago had a huge impact on botany. Subsequent discoveries provided unparalleled insights into early life on land. These include the earliest records of plant life cycles and fungal symbioses, the nature of soil microorganisms and the diversity of arthropods. Today the Rhynie chert (here including the Rhynie and Windyfield cherts) takes on new relevance, especially in relation to advances in the fields of developmental genetics and Earth systems science. New methods and analytical techniques also contribute to a better understanding of the environment and its organisms. Key discoveries are reviewed, focusing on the geology of the site, the organisms and the palaeoenvironments. The plants and their symbionts are of particular relevance to understanding the early evolution of the plant life cycle and the origins of fundamental organs and tissue systems. The Rhynie chert provides remarkable insights into the structure and interactions of early terrestrial communities, and it has a significant role to play in developing our understanding of their broader impact on Earth systems. This article is part of a discussion meeting issue 'The Rhynie cherts: our earliest terrestrial ecosystem revisited'.